Theory of Amplification of Sound (Acoustic Phonons) by Absorption of Laser Radiation in Quantum Wires with Parabolical Potential - Hung, Nguyen Quoc; Bau, Nguyen Quang (VNU Journal of Science: Mathematics - Physics, 2003)
Abstract